97.4k views
2 votes
-1 + 4 (6x + 3) = 1/2 (-10x - 10) -5

User Dmastylo
by
6.4k points

2 Answers

1 vote
x= 60/11 and totally didnt steal this answer lol
User Lunedor
by
5.7k points
5 votes

Answer: x = 60/11

Explanation:

-1 + 4 (6x + 3) = 1/2 (-10x - 10) -5

Multiply the 1/2 with -10x, and -10.

Let's look on the side that we are working on now.

New equation:

- 1 + 4 (6x + 3) = -5x - 5 - 5

-5-5= -10

-1+4(6x+3)=-10-5x

Next we remove the brackets.

-1 + 4 * 6x + 3 = -10x -5

Now we bring the x's on one side and the non-x's on the other. When we bring a positive x on the other side of an equal sign, it becomes negative. If we bring a negative x on the other side of an equal sign, it becomes positive.

10x * 6x = 1 - 4 - 3 - 5

60x = 1 - 12

60x = -11

x = 60/11

* I had to do this all on paper *

User Hololeap
by
6.0k points